Efficacy of herbicides under different methods of direct-seeded rice (Oryza sativa) establishments - SINGH, MANDHATA; SINGH, R P (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was conducted during rainy (kharif) season of 2006 and 2007 to study the efficacy of herbicides under different methods of direct-seeded rice (Oryza sativa L.) establishment. Establishment of rice by drum seeding significantly reduced the weed density and their dry weight and increased the yield-attributing characters finally led to 0.28 and 0.64 tonnes/ha higher rice yield over the wet (4.27 tonnes/ha) and dry seeding (3.91 tonnes/ha) of rice. Application of pretilachlor fb 2,4–D (0.75 fb 0.5 kg/ha) was most effective in lowering the weed density of grassy and non-grassy weeds and their dry weight, and thus enhancing yield attributes and yield (4.73 tonnes/ha) of rice. Weed control efficiency (84.23%) was maximum under this treatment compared with the other sequential application of herbicides, ie butachlor (71.90%) and pendimethalin (73.85%), followed by 2,4–D as well as their alone applications.